Meningkatkan Hasil Belajar Siswa Mata Pelajaran Tematik Melaui Metode Snowball Throwing - Nur Hakim (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
The purpose of this research is to know the use of the Snowball Throwing method in improving the result of fourth grade student learning at MI Al-Jihad Astana in thematic lesson theme 7 the beauty of Biotech in may Country of Brondong Lamongan Academic Year 2017-2018. The type of research data used in this study is the quantitative-qualitative approach (mexing method). The subjects of this study are class IV MI Al-Jihad Astana Brondong Lamogan Lessons year 2017-2018 amounted to 33 students. The techniques used in data collection are interview techniques, documentation, observation and tests. Based on the analysis and discussion it can be concluded that the use of the snowball Throwing method can improve the results of learning thematic lessons at MI Al-Jihad Astana Brondong Lamongan Lesson Year 2017-2018. This can be proven by the learning outcomes for each cycle. In cycle I, the average score of student learning test result is 67.73 the lowest value is 45.00 and the highest value is 90.00. It is known by comparing the pre-cycle values ​​with the Cycle I value, the test result where the Cycle value I is greater than the pre Cycle of the mean value, that is: 67.73> 55.30. While on the second cycle, the average value of the test is 75.91, while the lowest value was 55.00 and the highest value was 95.00. this can be known by comparing the value of the first cycle with the second cycle, the test results where the value of the second cycle test is greater than the first cycle of the average value of 75.91> 67.73. And in the third cycle it can be seen that the average value of the test results is 83.79, while the lowest value is 65.00 and the highest value is 100.00